Increasing Achievement Learning of Social Science on Islamic Kingdom Materials in Indonesia Through the Team Quiz Plus Method - Endang Susilowati; Sri Setyowati; R. Mendrika Vatosoa Idealy (International Journal of Geography, Social, and Multicultural Education, 2024)
The purpose of this study was to determine the increase in student achievement in social studies learning on the subject "Islamic Kingdoms in Indonesia" through the Team Quiz Plus method. the number of subjects in this research was 32 students. This research is a classroom action research in class VII B of SMPN 29 Gresik, East Java, which was conducted in 3 cycles. Cycles 1, 2 and 3 each consist of 2 face-to-face meetings. Each cycle includes the stages of planning (plan), action (action), observation (observation), and reflection (reflection). Data collection techniques are carried out by observation and documentation methods. The data collection instruments used were: 1) formative test questions; 2) student observation sheet. The results showed that the application of the Team Quiz Plus method was proven to be able to increase student achievement in social studies subjects on the material "Islamic Empires in Indonesia".